Implementation of The Siracusa Principles as Foundations for Reformulation of Social Restriction Policies in Public Health Emergencies - Rahadyan Fajar Harris; Natalia Carolina Simanjuntak (Universitas Negeri Semarang, 2022)
The purpose of this research is to implement the Siracusa Principles as the basis for the formulation and evaluation of public policies that have the potential to restrict people's rights and freedoms during social restrictions. This research uses the statutory and conceptual approaches of normative juridical methods as instruments of analysis. The findings of this paper include 667 cases of human rights violations released by LBH Jakarta throughout 2020. There are result of the government's social restriction policy to suppress COVID-19 transmission. Although Article 4 of the International Covenant on Civil and Political Rights (ICCPR) allows governments to restrict certain rights during public emergencies that threaten the life of the nation, states are not allowed to arbitrarily restrict people's rights and freedoms. Therefore, a mechanism is needed that can set restrictions on public rights in a balanced manner. In this regard, the Siracusa Principles can be implemented as a basis for the formulation of public policy through human rights due diligence and evaluating the government's compliance in implementing its policies. The novelty of this paper contains comprehensive discourses and recommendations in reformulating social restriction policies that are less friendly to human rights protection through restrictions on rights proportionally and internationally, and allow for the existence of check and balances mechanisms for the course of public policy. Therefore, with the implementation of the Siracusa Principles can be the basis for establishing restrictions on rights proportionally in order to develop policies of social restrictions and health quarantine that are more friendly to human rights protection and can minimize the occurrence of policy formulation errors that have the potential to violate human rights.